Pemahaman Nilai-Nilai Ajaran Islam Di Kampung Samate Kepulauan Raja Ampat - Mayalibit, M. Yasin Un.; Yusuf, Muhamad (Institut Agama Islam Negeri Fattahul Muluk Papua, 2020)
Moslems who are in the Raja Ampat Islands especially in the Samatevillage degraded understanding islamic especially among the young generation. They often interpret the teachings of Islam partially and misguided, it is realized or has not lowered Islam itself. The younger generations studied Islam (formal institutions) such as boarding schools, madrasah, and other Islamic colleges. In fact, leaving the prayers is considered commonplace, their presumed prayer of the body, which is important in heart. Understanding the value of Islamic teachings is declining in Samate village, North Salawati District, Raja Ampat Islands. The understanding of Islamic teachings in Samate Village influenced religious and customary figures that sought to collaborate between customs and religion, so as to defy the new understanding that entered, but fewer and less, influenced the development of the young generation's religious knowledge. Lack of interest in religious education, they are attracted by general knowledge and technology so that religious education is ruled out, tends to promote materialistic things. People who study religion are reluctant to return to live in Samate, no religious-based schools such as Madrasah or boarding schools in order to support the increasing religious knowledge of young generation. The external factor: Many villagers migrate to the city bringing the habit of unusual Village society, following the trend, lifestyle mode that emerged from the TV show, even the negative of the impressions are contrary to the customary value of society, which resulted in moral change and ethics of the younger generation.